Environmental Risk Disclosure and Cost of Equity - RIZKY ERIANDANI, 041517147302 (Czestochowa University of Technology, 2019)
Environmental problems are increasingly becoming a concern of various parties. When other studies look more at environmental performance, this study focuses on environmental risk disclosure. The purpose of this study is to empirically test the relationship of environmental risk with the cost of equity. Environmental risk disclosure is measured using content analysis. The cost of equity is calculated using the Capital Assets Pricing Model (CAPM) method. The study sample consisted of 476 companies listed on the Indonesia stock exchange in 2016-2018. The data is processed using SPSS with multiple linear regression methods. Empirical results show that environmental risk disclosure has a positive effect on the cost of equity. The results of this study contribute by expanding the disclosure theory because it empirically proves that investors use environmental risk information.